Tax morale after the reunification of Germany: results from a quasi-natural experiment - Lars P. Feld; Benno Torgler (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper provides a comparison of tax morale between inhabitants of East and West Germany in its post-reunification period, using three World Values Survey/European Values Survey waves between 1990 and 1999. German reunification is particularly interesting for the analysis of tax morale as it is close to a natural experiment. Many factors can be controlled because they are similar, as, e.g., a common language, similar education systems and a shared cultural and political history prior to the separation after the Second World War. As a consequence, an East-West comparison has a methodological advantage compared to crosscountry studies. Our findings show higher tax morale in East than in West Germany. However, in only 9 years after reunification, tax morale values strongly converged, especially due to a strong change in the level of tax morale in the East. We suggest that this convergence in tax morale between East and West Germany, despite efforts of the federal government to increase deterrence, indicates that tax morale is more strongly driven by other factors than deterrence.
Keywords: H26; H73; D78; C93; 330; Steuermoral; Steuerflucht; Soziale Werte; Vergleich; Alte Bundesländer; Neue Bundesländer; Nationale Einheit; Deutschland